Long-term efficacy and safety of vildagliptin add-on therapy in type 2 diabetes mellitus with insulin treatment. (January 2017) - Kanazawa, Ippei; Tanaka, Ken-ichiro; Notsu, Masakazu; Tanaka, Sayuri; Kiyohara, Nobuaki; Koike, Sayo; Yamane, Yuko; Tada, Yuko; Sasaki, Motofumi; Yamauchi, Mika; Sugimoto, Toshitsugu
Highlights: The long-term efficacy and safety of vildagliptin add-on therapy remains unclear. A 24-month, randomized study was conducted with type 2 diabetes treated with insulin. Vildagliptin reduced HbA1c the reduction was maintained for 24 months. The dose and number of insulin injections significantly reduced. Hypoglycemia was lower in the vildagliptin group than in the control group. Abstract: Background: The use of dipeptidyl peptidase (DPP)-4 inhibitors in patients with type 2 diabetes treated with insulin may be beneficial. However, the long-term efficacy and safety of vildagliptin add-on therapy in these patients remains unclear. Subjects and methods: A total of 73 patients with type 2 diabetes treated with insulin were randomly assigned to receive either add-on therapy of vildagliptin ( n = 37) or conventional therapy without DPP-4 inhibitors ( n = 36) for glucose control. Hemoglobin A1c (HbA1c) levels, dose and number of insulin injections, number of hypoglycemia episodes, and liver and renal function were monitored for 2 years. Results: The baseline characteristics of subjects, including age, dose of insulin injections, or HbA1c levels, did not differ between the two groups. In the vildagliptin group, HbA1c levels significantly decreased and the significance of HbA1c reduction was maintained for 24 months (from 8.0 ± 1.2% to 7.4 ± 1.0%, p < 0.05, at the end of observational period). In addition, the dose and number of insulin injections significantly reduced (−5.6 units, p < 0.01, and −0.9 times, p < 0.001). However, these parameters were unchanged in the control group. The number of patients who experienced three or more episodes of hypoglycemia per year was significantly lower in the vildagliptin group ( n = 4) than in the control group ( n = 11) (odds ratio, 0.28; 95% confidence interval, 0.08–0.97; p < 0.05). Conclusion: Vildagliptin as an add-on to insulin treatment for 24 months was well tolerated and led to sustained reductions in HbA1c, the dose and number of insulin injections, and the risk of hypoglycemia.